Political Party Performance: Election Systems in Developing and Developed Countries - Nofriadi, Nofriadi; Firsa, Pocut Zahran Nada; Ry, Mohd Dzaky; Fitriani, Rahma; Mahendra, Di Aidil (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This study aims to analyze the influence of electoral systems on political party performance by conducting a comparative study between developing and developed countries. Using a qualitative approach and secondary data analysis, this study explores how different electoral systems such as proportional and majoritarian systems affect political party dynamics, political representation, and voter participation. The findings show that developed countries with proportional electoral systems tend to produce more inclusive and responsive political parties, while developing countries often face challenges such as party fragmentation and low voter participation due to the majoritarian system. This study provides important insights for the development of more effective electoral systems and improving political party performance in both categories of countries.